Geospatial analyses in support of heavy metal contamination assessments of soil and grass along highways at Mafikeng, South Africa - Munyati, Chris (CONSAS, 2016)
Heavy metals in the environment are of concern due to detrimental effects, which include disturbance of plant physiology. This paper presents an exploratory assessment of heavy metal contamination along the main highways in Mafikeng, and illustrates how spatial analyses of the contamination for environmental management purposes can be supported by GIS and Remote Sensing. Roadside soil and grass (Stenotaphrum sp.) samples were analysed for total content per heavy metal. Spatial patterns in soil metal concentrations were evaluated using IDW interpolation. Effects of the contamination on the vigour of roadside grass were assessed using NDVI transects within 30m of the roads, on a pan-sharpened 5m resolution SPOT 5 HRG multispectral image. The results showed that NDVI values increased with distance from roads (R2 0.508-0.965; p < 0.05), indicating that proximity to roads reduced grass vigour. Metal concentrations in grass tissue were lower than in soil by an average factor of nine, but varied as the soil concentrations. The concentrations of the heavy metals that are associated with motor vehicles along roads were in the order [Fe]>[Mn]>[Zn]>[Pb]>[Ni]>[Cu]>[Cr]>[Cd], but were much lower than in cities that have higher motor vehicle traffic. IDW interpolation of metal concentrations revealed traffic-related spatial variations that can support environmental management. In this limestone mineralogy soil the relative abundance of Mn (range 2.4-11.4mg/kg) is attributable to lead replacement fuels that are in use, while the Pb concentrations (range 0.20-1.29mg/kg) indicate persistence of Pb in the urban environment some ten years after the phasing out of leaded petrol.